Uso de sensores remotos para estimación y análisis de subsidencia por extracción de agua subterránea en la Sabana de Bogotá (2017)
"This document presents the subsidence caused in the Bogota savanna due to the decrease in the groundwater level associated with the extraction of groundwater. I studied the climatic conditions and the characterization of El Niño weather event, one of the strongest ever recorded. This study took place between the beginning of 2015 and the middle of 2016. The results suggest a total subsidence of 2 cm (0.12 cm / month), associated with a total drawdown of 34 m (1.62 m / month), where the most important subsidence, occurred between September 2015 and January 2016 (2 cm / month). This has correlation with the series of precipitation and the drawdown found (33 m / month), where low values in precipitation, give significant decreases in the water table." -- Tomado del Formato de Documento de Grado.